2015
DOI: 10.1371/journal.pone.0138928
|View full text |Cite
|
Sign up to set email alerts
|

Being Sticker Rich: Numerical Context Influences Children’s Sharing Behavior

Abstract: Young children spontaneously share resources with anonymous recipients, but little is known about the specific circumstances that promote or hinder these prosocial tendencies. Children (ages 3–11) received a small (12) or large (30) number of stickers, and were then given the opportunity to share their windfall with either one or multiple anonymous recipients (Dictator Game). Whether a child chose to share or not varied as a function of age, but was uninfluenced by numerical context. Moreover, children’s givin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Several indirect pieces of evidence from our work suggest that there may be a unique impact of number knowledge, however: First, if other cognitive developments accounted for numerical cognition, we would expect to see a continued effect of age, after controlling for number knowledge. Second, smaller set sizes increased the rates of equal sharing behavior, showing that sharing behavior is affected by the inherent numerosity of the task (see Posid et al, 2015), even when other features of the task (e.g. vocabulary demands) were equivalent across trials.…”
Section: G Ener Al Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several indirect pieces of evidence from our work suggest that there may be a unique impact of number knowledge, however: First, if other cognitive developments accounted for numerical cognition, we would expect to see a continued effect of age, after controlling for number knowledge. Second, smaller set sizes increased the rates of equal sharing behavior, showing that sharing behavior is affected by the inherent numerosity of the task (see Posid et al, 2015), even when other features of the task (e.g. vocabulary demands) were equivalent across trials.…”
Section: G Ener Al Discussionmentioning
confidence: 99%
“…They are also quick to recognize when others have violated norms of equal sharing behavior (Geraci & Surian, ; LoBue, Nishida, Chiong, DeLoache, & Haidt, ; Olson & Spelke ; Rakoczy, Kaufmann, & Lohse, ; Schmidt & Sommerville, ; Sloane, Baillargeon, & Premack, 2011; Ziv & Sommerville, ). Yet, when given the chance to act on these beliefs, it is striking that young children fail to actually share fairly with others in many contexts (Blake & McAuliffe, ; Fehr, Bernardt, & Rockenbach, ; Kogut, ; McAuliffe, Blake, Kim, Wrangham, & Warneken, ; Posid, Fazio, & Cordes, ; Shaw et al., ). That is, in spite of the importance that children place on equal sharing during the first few years of life, the behavioral manifestation of fairness is a relatively later‐developing phenomenon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that differences in infants’ altruistic tendencies could be related to their fairness concerns. Altruism is defined as a behavior that benefits others at a cost to the self (e.g., Grusec, Davidov, & Lundell, ), and studies have revealed that children's altruism in the dictator game is influenced by considerations of a resource's value: Children are more generous when distributing their least favorite stickers compared to their most favorite stickers (Blake & Rand, ), when distributing items that required a relatively small rather than large amount of effort to obtain (Benozio & Diesendruck, ), or when resources are plentiful versus scarce (Posid, Fazio, & Cordes, ). Similarly, toddlers will more readily help an experimenter by handing her a toy that belongs to her rather than by giving up their own favorite toy from home (Svetlova, Nichols, & Brownell, ).…”
Section: Children's Fairness Concerns and Moral Developmentmentioning
confidence: 99%